The rough patch : marriage, midlife, and the art of living together - De Marneffe, Daphne, 1959- (Scribner, 2018)
Outlines a radical, optimistic approach to marriage designed to balance personal needs with the sometimes relentless demands of a relationship, addressing challenges ranging from parenthood and health to fidelity and aging.